Budesonide/formoterol for maintenance and reliever therapy: new quality in asthma management. Issue 4 (July 2008) - Kuna, Piotr; Kuprys-Lipinska, Izabela
Asthma is a chronic inflammatory disease of the airways with variable symptoms and airway obstruction. The strategy of asthma management aims to prevent and relieve acute attacks and achieve long-term control of symptoms. Symbicort ®® is a fixed combination of the corticosteroid budesonide and the long-acting ββ2 -agonist formoterol –– the first component treats inflammation, the second provides rapid and long-term smooth muscle relaxation. These two components make budesonide/formoterol suitable for both maintenance and reliever asthma therapy (Symbicort SMART ®® ). There is increasing evidence from clinical trials that such a regimen is an effective and safe treatment option. The patient taking budesonide/formoterol for symptom relief simultaneously increases the dose of inhaled corticosteroids. Therefore, the pharmacological intervention provides an earlier step up in controller therapy, just prior to asthma deterioration, and thus prevents exacerbations. Such a regimen better reflects the nature of asthma and allows patients to match the anti-inflammatory dose to the patient''s actual clinical state. Moreover, SMART is a more convenient regimen for patients and may increase therapy compliance. SMART is a new quality in asthma management and may become the future gold standard in asthma treatment.